Tâvûs b. Keysân ve Hadis ilmindeki yeri - Yüksel, Furkan (My University, 2017)
TÂVÛS B. KEYSÂN VE HADİS İLMİNDEKİ YERİ Tabiînin ilk tabakalarından sayılan Tâvûs b. Keysân (ö. 106/ 725) Yemen’de doğup ilmi gelişimini farklı yerlerde tamamlayarak Mekke’de hicri 106 yılında vefat etmiştir. “İmam”, “fakih” ve “hafız” unvanlarıyla nitelenen Tâvûs b. Keysân Yemen’de doğup büyümesine rağmen farklı bölgelerden birçok hocanın tedrisatından geçmiş ve birçok talebeye hocalık yapmıştır. İbn Abbas (ö. 68/ 687-88), İbn Ömer (ö. 73/ 692), Ebû Hureyre (ö. 58/ 678) gibi hadis rivayetinde ve dirayetinde önde gelen sahabilerin eğitiminden geçerek onların seçkin talebeleri arasında yer almıştır. Bu çalışmada Yemen ve Mekke ilim dünyasını somut olarak görme açısından Tâvûs’un hadisçiliği incelenmiştir. Tâvûs’a dair bu çalışmada Tâvûs’un yaşadığı ortam ve zaman dilimi ilmî, siyâsî, sosyal açılardan ele alınmış, sonrasında ise Tâvûs’un hadisçiliğini tespit adına hoca-talebe ilişkileri, söz ve uygulamaları yoluyla hadis iii ve sünnet anlayışı, rivâyetlerine dair veriler incelenmiştir. Bu araştırmalar neticesinde Tâvûs’un tabiîn neslinde önde gelen muhaddislerden olduğu özellikle de İbn Abbas’ın pek çok rivayetinin günümüze ulaşmasında ve onun düşünce yapısının intikalinde etkin rol oynadığı söylenebilir. Keysân, İbn Abbâs, tabiîn, hadis, Yemen, Mekke

TAWUS B. KAYSAN AND HIS PLACE IN HADITH SCIENCE Tawus b. Kaysan was born in Yemen and is counted as belonging to the earliest of the tabiîn. He completed his scholarly training in different places and died in Mecca in 106 hijri. Awarded the titles imam, faqih and hafiz, although Tawus b. Kaysan was born and raised in Yemen, he was educated by many different teachers from different regions and taught many subjects. It is known that he earned his education from leading sahaba in the narration of hadith and wisdom, such Ibn Abbas, Ibn Umar, Abu Hurayra, as one of their chosen students. In this study, the hadith of Tawus is examined in terms of seeing concretely the scholarly world of Yemen and Mecca. In this study, the environment and time period in which Tawus lived is studied in terms of its scientific, political and social aspects. Later, to understand his approach to narrations and thoughts on hadith and sunnah, teacher-student associations, and words and methodological practices are respectively studied. In addition, information about his narrations and, finally, social network is examined. As a result of these v investigations, it can be stated that Tawus is one of the leading writers from the tabiîn generation, and more especially, it can be said he played a influential role regarding many of the narrations from Ibn Abbas that have reached us today and in the transmission of the structure of Ibn Abbas thought. Key words: Tâwûs b. Kaysân, Ibn Abbâs, tabiîn, hadith, Yemen, Mecca
Keywords: Hadis; Hadis hadith; İslam dini; Tâvûs b. Keysân, (ö. 106/ 725)